“Paylaşma Tutum Ölçeği” Geçerlilik Çalışması ve Bazı Değişkenlerle İlişkisi / “Sharing Attitude” Scale Validation and the Relationship with Some Variables - Karakaş, Ahmet Canan (Journal of History Culture and Art Research, 2017)
Abstract In this research, the effects of “Sharing attitude”, a religious and human value, on the mental health of the individual are examined. As a religious value, “Sharing” includes help and goodwill made for the sake of God. The best describing terms the concept of “sharing” are "infaq/donation” and "sadaqah/charity". As a human value, "Sharing" manifests in different appearances like empathy, altruism, conscience, and compassion. This research includes some analysis of the "Sharing Attitude Scale" which developed to determine the effects of "sharing" as both a religious and a human value on the individual's mental health. The study examines the relationship of “sharing attitude” with some selected variables. The scale has been enhanced aiming at a universal sample. The research universe is Karabük and cluster sampling is used in the selection of the sample. A sample number that could represent the universe with 95% confidence level and 5% error margin was targeted and 401 samples were reached. The collected data has been analysed with SPSS 22 software. The scale includes three sub-dimensions of sharing: 1- instutional sharing, 2- personal sharing and 3- social sharing. Some figures obtained from the survey are as follow: Kaiser Meyer Olkin=0.800, Bartlett's Test of Sphericity= 885,529, df= 91, p= 0.000. As for reliability analysis, the Cronbach’s Alfa figure is calculated as 0,76. As for the sub-dimensions, the figures of Cronbach’s Alfa calculated as follows: For the instutional sharing α=736, for the personal sharing α=496, for the social sharing α=644. Öz Bu araştırmada, dini ve insani bir değer olarak paylaşmanın bireyin ruh sağlığına etkileri incelenmektedir. Dini bir değer olarak paylaşma, Allah rızası gayesiyle yapılan yardım ve iyilikleri kapsar. Dini bağlamda paylaşma kavramını en iyi açıklayan kavram “infak” ve buna bağlı olarak da “sadaka” kavramlarıdır. İnsani bir değer olarak “paylaşma” ise empati, diğergamlık, vicdan, merhamet gibi farklı görünümlerde tezahür eder. Bu araştırma hem dini ve hem de insani bir değer olarak “paylaşma”nın bireyin ruh dünyasına etkilerini belirlemek için geliştirilen “Paylaşma Tutum Ölçeği” ile ilgili bazı analizleri ihtiva etmektedir. Araştırmada paylaşma tutumunun seçilen bazı değişkenlerle ilişkisi incelenmiştir. Ölçek, genel örneklem hedeflenerek geliştirilmiştir ve ilk defa uygulanmıştır. Araştırma evreni Karabük ili olup örneklem seçiminde alan örneklemesi kullanılmıştır. Evreni %95 güvenilirlik düzeyi ve %5 hata payı ile temsil edebilecek bir örneklem sayısı hedeflenmiş ve 401 örnekleme ulaşılmıştır. Veriler, SPSS programıyla analiz edilmiştir. Ölçek, Kurumsal Paylaşma, Bireysel Paylaşma ve Sosyal Paylaşma alt boyutlarını içermektedir. Araştırmada elde edilen değerler Kaiser Meyer Olkin = 0.800, Bartlett's Test of Sphericity=885,529, df= 91, p=0.000 şeklindedir. Cronbach’s Alfa değeri ise 0,76 olarak hesaplanmıştır. Alt boyutların Cronbach’s Alfa değerleri Kurumsal al boyut için α=736, Bireysel Paylaşma alt boyutu için α=496, Sosyal Paylaşma alt boyutunun ise α=,644 şeklinde hesaplanmıştır.